Evidence for Age-Equivalent and Task-Dissociative Metacognition in the Memory Domain - Zakrzewski, Alexandria C.; Sanders, Edie C.; Berry, Jane M. (Frontiers in Psychology, 2021)
Research suggests that metacognitive monitoring ability does not decline with age. For example, judgments-of-learning (JOL) accuracy is roughly equivalent between younger and older adults. But few studies have asked whether younger and older adults’ metacognitive ability varies across different types of memory processes (e.g., for items vs. pairs). The current study tested the relationship between memory and post-decision confidence ratings at the trial level on item (individual words) and associative (word pairs) memory recognition tests. As predicted, younger and older adults had similar metacognitive efficiency, when using meta-d’/d’, a measure derived from Signal Detection Theory, despite a significant age effect favoring younger adults on memory performance. This result is consistent with previous work showing age-equivalent metacognitive efficiency in the memory domain. We also found that metacognitive efficiency was higher for associative memory than for item memory across age groups, even though associative and item recognition memory (d’) were statistically equivalent. Higher accuracy on post-test decision confidence ratings for associative recognition relative to item recognition on resolution accuracy itself (meta-d’) and when corrected for performance differences (meta-d’/d’) are novel findings. Implications for associative metacognition are discussed.